Enhanced corrosion resistance of the surface modified Ti-13Nb-13Zr alloy by ultrasonic shot peening. (15th August 2021) - Kumar, Pramod; Mahobia, G.S.; Mandal, Sumantra; Singh, V.; Chattopadhyay, Kausik
Highlights: Ultrasonic shot peening (USSP) successfully developes nanostructure at the top surface of the alloy Ti-13Nb-13Zr. Compressive residual stress at the top surface increases with duration of USSP treatment. All the USSP treated samples showed improvement in corrosion resistance. Titanium oxide was identified as main corrosion product. Abstract: The near-β Ti-13Nb-13Zr alloy was processed by ultrasonic shot peening (USSP) for different durations of 15–120 s to develop surface nanostructure. The effect of the USSP was studied on its corrosion behaviour in Ringer's solution, by electrochemical impedance spectroscopy and potentiodynamic polarization tests. The electrochemical study revealed reduction in corrosion of the USSP treated samples. There was maximum passivation in the 30 s of USSP treatment, while it decreased with an increase in USSP duration. The improvement in the corrosion resistance from USSP was due to grain refinement and the associated compressive residual stresses in the surface region.